Pengaruh Ekonomi Digital Terhadap Pendapatan UMKM Kota Serang dengan Literasi Digital Sebagai Variabel Moderasi - Wijaya, Herman; Nailufaroh, Lulu (Departement Of Accounting, Indonesian Cooperative Institute, Indonesia, 2022)
Micro, Small, and Medium Enterprises are one of the drivers of development and economic growth in Indonesia. This study aims to examine the influence of the digital economy on the income of Small Medium Enterprise Business in the city of Serang with digital literacy as a moderating variabel. Descriptive qualitative method is the method that I use in this research with the sample used is people who are registered as members of the “Rumah Kreatif BUMN” in Serang City and use internet media in their business activities both in promotional activities or transactions. The number of samples as respondents from this study amounted to 338 respondents. The analytical tool used was Smart PLS version 3.0. The results of this study prove that the digital economy has a positive and significant effect on the income of Small Medium Enterprise business in the city of Serang. And the role of digital literacy is significant in moderating the relationship between the two variabels. This indicates that the income of Small Medium Enterprise Business will increase if digital literacy is maximized.